Endoscopic Management of Branchial Fistula: Diagnostic and Therapeutic. - Paul, Mark; Goh, Bee See (IIUM Medical Journal Malaysia, 2021)
Recurrent neck abscess is a typical feature of branchial anomaly. Open surgical excision has been the primary treatment modality for past decades however several alternative treatment modalities such as endoscopic electrocauterization has recently gained popularity and acceptance universally. This series aims to introduce endoscopic assessment as the first line diagnostic and therapeutic management for branchial fistula. 5 patients underwent examination under general anesthesia via direct laryngoscopy, endoscopic assessment and cauterization in our centre from 2016 to 2019. They were then followed up at our clinic to assess disease progression. Comparison between open neck surgery and endoscopic cauterization of internal sinus tract opening as the primary treatment has reported similar recurrence rate. Proposal of endoscopic assessment as the first line investigation and diagnostic tool with the aim of therapeutic cauterization at the same setting. MRI may be needed in scenarios such as failed endoscopic treatment or when open surgery is required.